(untitled) (TEST XY. Critical review of studies on the representation of architecture and use of the image in science and art, 2017)
Three unpublished typewritten documents were found in Lucio Saffaro’s home after his death, which took place in 1998 in Bologna, and now they are printed in these pages. The cataloguing and subsequent archiving, by Saffaro Foundation, ended in 2004 and revealed a lot of unpubli- shed literary writings that are collected and stored in thirteen folders. However, Zero della meditazione contraddittoria, La Nuova Metafisica, as well as the dedicated to painting text, are without date, but we may assume that they can date back to the years 1957–1960, as they were found in a binder on which the author had written: ANCIENT ESSAYS TO BE ORGANIZED. In the same binder, indeed, another typewritten document shows “1957”, which confirms the place- ment of these writings in youth; the style, the metaphorical forms, the metaphysical atmospheres and the existential statements could also confirm the date. (Gisella Vismara) The eighteen selected images as complement of the three texts are published by courtesy of the Lucio Saffaro Foundation in Bologna.